2010
DOI: 10.1007/s11240-010-9795-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of triploid plants of papaya by endosperm culture

Abstract: Triploid papaya (Carica papaya) plants were obtained by immature endosperm culture. Visible callusing of the endosperm occurred 21 days after initiation of cultures. A continuously growing callus was observed and a maximum of 68.7% of callus induction frequency was obtained when immature endosperm with embryo was cultured on Murashige and Skoog (MS) medium containing 6.0 lM 2,4-dichlorophenoxyacetic acid (2,4-D), 2.5 lM a-naphthaleneacetic acid (NAA) and 4.0 lM 6-furfurylamino purine (Kn). Shoot buds were prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
4
18
0
Order By: Relevance
“…The basal media comprised Murashige and Skoog (MS) medium (Murashige and Skoog 1962), 3 g/ L gelrite and 30 g/L sucrose, with pH adjusted to 5.7-5.8. Autoclaved growth media were supplemented with established (Sun et al 2011) concentrations of plant growth regulators: 1.5 mg/L 2,4-dichlorophenoxy acid (2,4-D), 0.5 mg/L a-naphthaleneacetic acid (NAA), 2.25 mg/L benzylaminopurine (BAP) and 1 mg/L kinetin for callus induction. Induction of somatic embryos was performed using regeneration media consist of 0.02 mg/ L NAA and 0.1 mg/L BAP at 25 ± 1°C in the light.…”
Section: Induction Of Embryogenic Callusmentioning
confidence: 99%
See 1 more Smart Citation
“…The basal media comprised Murashige and Skoog (MS) medium (Murashige and Skoog 1962), 3 g/ L gelrite and 30 g/L sucrose, with pH adjusted to 5.7-5.8. Autoclaved growth media were supplemented with established (Sun et al 2011) concentrations of plant growth regulators: 1.5 mg/L 2,4-dichlorophenoxy acid (2,4-D), 0.5 mg/L a-naphthaleneacetic acid (NAA), 2.25 mg/L benzylaminopurine (BAP) and 1 mg/L kinetin for callus induction. Induction of somatic embryos was performed using regeneration media consist of 0.02 mg/ L NAA and 0.1 mg/L BAP at 25 ± 1°C in the light.…”
Section: Induction Of Embryogenic Callusmentioning
confidence: 99%
“…The availability of completed 372 Mbp papaya genome with various bioinformatics tools and resources accelerates the identification of genes involved in important biological processes (Ming et al 2008). Molecular studies in papaya have been facilitated by the establishment of in vitro culture and transformation system, including numerous studies in callus induction and regeneration from various explants (Ascencio-Cabral et al 2008;Bhattacharya and Khuspe 2001;Chen and Chen 1992;Chen et al 1987;Fitch et al 1993;Conover 1981, 1982;Sun et al 2011;Yu et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thammina et al (2011) reported that callus was not induced with Euonymus alatus endosperm on hormone-free MS medium. Sun et al (2011) also reported that all papaya (Carica papaya) explants turned brown and died without any sign of growth on basal medium. Tian et al (2012) reported that high callus formation rates (approx.…”
Section: Endosperm Culture In Vitromentioning
confidence: 97%
“…Embryo rescue was utilized by plant breeders to rescue inherently weak, immature and/ or abortive embryos, breeding seedless crosses and triploid plants, and distant hybridization between different species (Sharma 1995). Thus far, embryo rescue was extentively applied in rescuing many fruit crops, including apple (Dantas et al 2006), banana (Uma et al 2011), citrus (Viloria & Grosser 2005;Aleza et al 2012), grape (Sun et al 2011), etc. Li et al (2015 provided an overview of the factors that affect its efficiency, including genotype, the time point of removing ovules, medium, culture method and condition, plant growth regulators, etc.…”
Section: Artificial Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation